Koreans in Minnesota - Ryu, Sooh-Rhee, 1979- (Book collections on Project MUSE., 2019)
"Koreans in Minnesota introduces readers to the history of Korean immigration here, including settlement patterns and the formation of religious and social communities. Organizations ranging from the Korean American Association of Minnesota--the cornerstone of Korean immigrant society--to the Korean Service Center, which provides social services to elderly Koreans, to AK Connection, a networking alliance of adult adopted Koreans, to educational groups and institutions that teach the Korean language and culture help to tell the stories of this varied group"--